Clinical Examination in Orthopedics - Iyer, Mohan; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
This book has been written step wise by enumerating various aspects of the importance of clinical examination derived by laying one$1 (Bs hands on the affected part. By a thorough clinical examination, it can help an individual to arrive at a tentative differential diagnosis of the condition and hence help in investigating the same by numerous tests which are relevant to the given condition. The manner in which a given case is handled in this way is far more important than the diagnosis of the condition and this feature comes with practicing the same many times. It is a must for anyone embarking in life on Orthopedics as a career.s
Examination of diseases of bone -- Examination of the Shoulder -- Examination of the Elbow -- Examination of the Wrist and Fingers -- Examination of the Hip and the pelvis -- Examination of the knee -- Examination of the Ankle and foot -- Examination of the Cervical Spine -- Examination of the Lumbar Spine -- Examination of the Temporomandibular joint -- Examination of Gait.
Keywords: Medicine; Orthopedics; Orthopedic surgery; Medicine & Public Health; Orthopedics; Surgical Orthopedics; Conservative Orthopedics